The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services and the challenge of integrating social sciences and humanities - Stenseke, Marie (Bulletin of Geography. Socio-economic Series, 2016)
For the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES), established in 2012, under the auspices of four United Nations entities (FAO, UNDP, UNEP and UNESCO), there is an urgent need to engage scholars in social sciences and humanities in assessing the state of the planet's biodiversity. This article addresses the fundaments for involving scientists from these fields of science in IPBES, and reflects on the existing barriers. It builds on previous research on IPBES from various perspectives, as well as on the author's insights from work in the organization. A fundamental condition recognized is that there needs to be a qualified understanding of what it means to integrate natural sciences and social sciences/humanities, and also that the latter have to be accepted on their own terms. Other barriers are related to the contextualisation of biodiversity issues and the more politically sensitive character of research carried out in social sciences and humanities. In the conclusions it is emphasized that the deliverables of the first round of IPBES assessments have to be solid enough from the perspectives of social sciences and humanities, in order to attract more of these scholars to work for the platform in the future.